Dopamine receptor DRD4 gene and stressful life events in persistent attention deficit hyperactivity disorder. Issue 6 (14th July 2015) - Sánchez‐Mora, Cristina; Richarte, Vanesa; Garcia‐Martínez, Iris; Pagerols, Mireia; Corrales, Montse; Bosch, Rosa; Vidal, Raquel; Viladevall, Laia; Casas, Miguel; Cormand, Bru; Ramos‐Quiroga, Josep Antoni; Ribasés, Marta
Abstract : We performed a case‐control association study in persistent ADHD considering eight candidate genes ( DRD4, DAT1/SLC6A3, COMT, ADRA2A, CES1, CYP2D6, LPHN3, and OPRM1 ) and found additional evidence for the involvement of the Dup 120bp and VNTR 48bp functional variants within the dopamine receptor DRD4 gene in the etiology of adult ADHD. We subsequently investigated the interaction of stressful life events with these two DRD4 polymorphisms, and the impact of such events on the severity of ADHD symptomatology. The gene‐by‐environment analysis revealed an independent effect of stressful experiences on the severity of persistent ADHD, and a gene‐by‐environment interaction on the inattentive dimension of the disorder, where non carriers of the Dup 120bp (L) ‐ VNTR 48bp (7R) haplotype were more sensitive to environmental adversity than carriers. These results are in agreement with previous works reporting a relationship between DRD4 and the effect of adverse experiences, which may explain the discordant findings in previous genetic studies and strengthen the importance of gene‐by‐environment interactions on the severity of ADHD. © 2015 Wiley Periodicals, Inc.